Knowledge, attitudes and practices of pregnant mothers about anemia at the Centro de Salud San Luis - 2022, Lima - Rocío Alejo (2025)
The objective of this study is to determine the level of knowledge, attitudes and practices about anemia in pregnant women at the Centro de Salud San Luis. The research was quantitative, descriptive, correlational and cross-sectional. The total number of participants was 77 pregnant women who attended their prenatal check-ups in the months of January-February (2023). They were given a validated questionnaire distributed in 2 parts, general data and dietary regime. It was found that the percentages of hemoglobin in pregnant women were 61.1% (47) without anemia, 31.1% (24) mild anemia and 7.8% (6) moderate anemia. Regarding their knowledge, it was found that 58.4% (45) was good, 37.7% (29) fair and 3.9% (3) bad. Regarding their attitudes, 93.5% (72) were positive and 6.5% (5) negative. Finally, in their practices, 97.4% (75) were adequate and 2.6% (2) inadequate. The data were analyzed with the Jamovi program, version 2.6.22 using the chi-square test and a significant relationship was found between the level of anemia and knowledge, attitudes and practices. In addition, it was obtained as a result that the pregnant women had good knowledge, positive attitudes and adequate practices about anemia.